Age, period and cohort effects on mortality from cervical cancer in Colombia between 1985 and 2014. (Colombia Medica, 2022)
Objective:To analyze cervix cancer mortality in Colombia based on age, period, and cohort effects.Methods:The mortality and population data were taken from the official databases of the National Administrative Department of Statistics, DANE. Five models were adjusted, and the significance of the effects was obtained by comparing them through the likely ood ratio test.Results:The age-adjusted mortality rate in deaths was 15.09/per 100,000 women in 1985-1989 and 10.21 in 2010-2014. The annual percentage average change was -1.45% (95% CI: -1.57% to -1.34%). Age, period, and cohort effects were found.Conclusions:Demographic factors could explain the behavior of cervical cancer mortality in Colombia and the establishment of public health measures in the last two decades.